Nomenclatural novelties in Baccharis subgen. Molina (Asteraceae, Astereae) - Heiden, Gustavo (Phytotaxa, 2019)
The number of species recognized in Baccharis Linnaeus (1753: 860), a Neotropical genus characterized by the tufted indumentum of leaves and stems and by the unisexual florets generally in separate specimens (Müller 2006), ranges from 354 (Müller 2013) to ca. 500 species (Malagarriga 1976). The infrageneric classification (Heiden 2014, Heiden & Pirani 2016) currently recognizes seven subgenera: Baccharis subgen. Baccharis, Baccharis subgen. Coridifoliae (Giuliano in Giuliano & Freire 2011: 339) Heiden in Heiden & Pirani (2016: 286), Baccharis subgen. Heterothalamulopsis (Deble et al. 2004: 1) Heiden in Heiden & Pirani (2016: 287), Baccharis subgen. Heterothalamus (Lessing 1830: 145) Heiden in Heiden & Pirani (2016: 288), Baccharis subgen. Molina (Persoon 1807: 424) Heering (1904: 40), Baccharis subgen. Oblongifoliae (Candolle 1836: 416) Heiden in Heiden & Pirani (2016: 289), and Baccharis subgen. Tarchonanthoides Heering (1904: 26).